A quaternary metal–metalloid–nonmetal electrocatalyst: B, P-co-doping into PdRu nanospine assemblies boosts the electrocatalytic capability toward formic acid oxidation. Issue 5 (17th January 2020) - Xu, You; Yu, Shanshan; Ren, Tianlun; Li, Chunjie; Yin, Shuli; Wang, Ziqiang; Li, Xiaonian; Wang, Liang; Wang, Hongjing
Abstract : Quaternary PdRuBP nanospine assemblies (PdRuBP NAs) were readily synthesized and they exhibited enhanced electrocatalytic performance toward the formic acid oxidation reaction. Abstract : The development of highly active, durable and cost-effective electrocatalysts toward the formic acid oxidation reaction (FAOR) is meaningful for direct formic acid fuel cell technology. In this work, we develop a facile one-pot strategy based on a NaH2 PO2 –NaBH4 –DMF reaction system for B, P-co-doping into pre-synthesized PdRu nanospine assemblies (PdRu NAs), resulting in quaternary PdRuBP NAs. The synergism of hyperbranched nanoarchitectonics and quaternary metal (Pd, Ru)–metalloid (B)–nonmetal (P) composition of PdRuBP NAs largely boosts their electrocatalytic capability for the FAOR, with enhanced activity and durability and improved tolerance toward COads . The research results may add to a growing toolbox of important doping strategies that yield metal nanocrystals doped with two or more selected metalloid and/or nonmetal elements, offering unique capabilities for property/functionality optimization.